Management of persistent air leak in Neonates: A case series - Jimmy Israel Andrade- Montesdeoca; Vicente Salinas- Salinas; Daniel Acosta- Farina; Daniel Acosta- Bowen (EL-Med-Pub, 2023)
Background: Autologous blood patch pleurodesis (ABPP) has been used in adults as an efficient and safe technique to address persistent air leak (PAL). A fibrin glue patch is also an alternative, but its elevated cost and technique can limit its routine use. Evidence of their use in the pediatric population, specifically in the neonatal age is scant. Case Presentation: We share our management experience in a series of 3 cases. The first 2 were treated exclusively with ABPP and showed clinical and radiographic improvement. The 3rd case, due to the persistence of the air leak, required extended thoracotomy and fibrin patch placement. Conclusion: The use of ABPP as an alternative for the treatment of neonates with PAL is a safe and efficient technique. The procedure is replicable and can be done at the bedside at a low cost. A fibrin glue patch should be considered as an alternative option when ABPP fails to resolve the leak.